Responses to Fetal Heart Rate Alarms on a Busy Tertiary Labor and Delivery Unit [12R]. (May 2018) - Ona, Samsiya; Greenberg, James A.
Abstract : INTRODUCTION: Alarm fatigue is a well-recognized phenomenon that has been demonstrated to impede rather than promote patient safety. This study investigates the incidence of electronic fetal heart rate (FHR) monitor alarms and staff responses. METHODS: The FHR monitor database from the labor and delivery (L&D) unit was queried to determine the number and duration of alarms/day over the course of 7 consecutive days. In addition, a survey was sent to L&D care providers to determine their subjective impression of how often the alarms were activated and their action if any. RESULTS: Over 7 consecutive days, there were 130 deliveries associated with 4981 alarm events with a cumulative total of 103 hours of alarms (average 15 alerts/hr totaling cumulative average 7.4 hrs/day). Surveys were sent to 322 staff with responses from 159 (49%). Thirty-four (21.4%) surveys were incomplete. Of respondents 69% (110) had the subjective impression that the alarms were ringing either "often" or "almost all the time." Of those only 59% took some action while 41% ignored or hardly noticed the alarms. CONCLUSION: In this study of a high-volume academic hospital L&D unit, our data show that FHR monitor alarms are ringing every 4 minutes for a cumulative total of about 1/3 of the day. However, these alerts are ignored by almost half of the staff. Consequently, we believe that either the use of FHR monitor alarms or the policies and procedure regarding those alarms should be reviewed to ensure that their use is having a positive impact on patient safety.